The art of naming: a Muslim woman's Journey - Abdul Manaf, Nor Faridah (Awards Publishing, 2006)
This collection of bilingual poems (Englisha nd Malay) depicts the journey of a Muslim woman who writes of her student days, travels, marriage, family, career life and her encounters with men who may or may not support women's position in the public life.